Inclusive food system transformations for healthy diets: National experiences with a global challenge - CGIAR Research Program on Agriculture for Nutrition and Health (International Food Policy Research Institute, 2020)
The CGIAR Research Program on Agriculture for Nutrition and Health (A4NH) is dedicated to the realization of Sustainable Development Goals 2 and 3, as coordinated by the United Nations and agreed to by member countries. These goals include objectives to: end hunger, achieve food security and improved nutrition, promote sustainable agriculture, ensure healthy lives, and promote well-being for all at all ages.